Охранные исследования 2008 г. на территории Мемориала «Поле Альминского сражения» - Пуздровский, А.Е.; Ляшук, П.М.; Медведев, Г.В. (Археологічні дослідження в Україні, 2009)
The article is devoted to the protective research on the territory of the Memorial «Battlefield of Alma Battle» (Vilino village of Bakhchisaray Region in the Crimea).